Recuperación internacional del patrimonio ancestral del Ecuador por tráfico ilícito de bienes culturales - León Aldas, Nicole Elizabeth (2021)
The present study, entitled 'International Recovery of the Ancestral Heritage of Ecuador due to the Illicit Trafficking of Cultural Property', deals with one of the most profitable criminal conduct in the world, resulting in the loss of property, because it promotes the destruction of sites and sites that directly affect the material and intangible heritage of peoples and communities. The main objective is to analyse the international instruments, to which Ecuador is currently a signatory, against trafficking in cultural property, and thus to examine the possibility of introducing a recovery mechanism, reparation, compensation or compensation in the Organic Code Integral Penal, to whom it traffics ancestral heritage..........